Paz justa: a contribuição do Cristianismo no pensamento para a paz - Silva, Joyce Kelly Costa (2019)
This dissertation seeks to examine the validity of the Christian religion as a variable to understand the construction of peace and how that religion can contribute to this field from the concept of just peace. Just peace emphasizes peace and justice as central elements both to prevent war and to build peace after its end. This approach critically confronts the old tradition of just war as one that does not contemplate post-war issues or the construction of sustainable peace and rescues Christianity's original peaceful position. Bearing in mind that just peace emphasizes peace and justice as central elements, firstly what will be discussed is “peace” and how this concept is treated on the international stage. Second, the new literature that brings religion as an important variable for International Relations will be explored, and the insertion of this theme in discussions about peace building. Finally, the idea of just peace and the elements of the Christian religion that underlie this approach will be discussed. In addition, some cases will be explored in which Christians contributed to the construction of post-war peace and the peaceful transformation of conflicts.